2021 IEEE/ACM 43rd International Conference on Software Engineering: Software Engineering Education and Training (ICSE-SEET) 2021
DOI: 10.1109/icse-seet52601.2021.00035
|View full text |Cite
|
Sign up to set email alerts
|

To Get Good Student Ratings should you only Teach Programming Courses? Investigation and Implications of Student Evaluations of Teaching in a Software Engineering Context

Abstract: Student evaluations of teaching (SET) are commonly used in universities for assessing teaching quality. However, previous literature shows that in software engineering students tend to rate certain topics higher than others: In particular students tend to value programming and software construction over software design, software engineering models and methods, or soft skills. We hypothesize that these biases also play a role in SET responses collected from students. The objective of this study is to investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…This preconception echoes previous findings that students think non-technical skills are unnecessary for technical careers [32]. While educators and employers agree with the importance of soft skills, our findings suggest staff do not perceive students to recognise the value of soft skills, aligning with previous findings where students undervalue soft skills [10] in favour of the skills they enjoy [37].…”
Section: Staff Perceptions Of How Soft Skills Aresupporting
confidence: 84%
See 2 more Smart Citations
“…This preconception echoes previous findings that students think non-technical skills are unnecessary for technical careers [32]. While educators and employers agree with the importance of soft skills, our findings suggest staff do not perceive students to recognise the value of soft skills, aligning with previous findings where students undervalue soft skills [10] in favour of the skills they enjoy [37].…”
Section: Staff Perceptions Of How Soft Skills Aresupporting
confidence: 84%
“…Students also conflate enjoyment with value during tasks [37] and so if students have a negative experience with an activity or project that they associate with soft skills, they will attach a lower value to these soft skills, in favour of tasks and activities that they see as more enjoyable. This may feed into their conception that technical skills are more important [33], for example programming tasks can be typically autonomous alleviating the need for collaboration with others, and it can be satisfying to solve problems through code.…”
Section: Student and Graduate Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the teaching of introductory programming effectively has persistent issues [3,17,22], attrition and failure rates can be high, with a range of issues impacting barriers to progression [30]. Student satisfaction as measured by satisfaction surveys is reported as commonly below that of other disciplines [23] and varies across the discipline with some subdiscipline areas facing particular challenges to navigate [13]. Discipline related challenges linked to delivering teamwork are also reported [7,19].…”
Section: Why Are You Doing It?mentioning
confidence: 99%
“…For example, they have been shown to be influenced by a number of irrelevant factors such as the faculty's sex gender, race/ethnicity, and even the presentation of cookies during their completion (Al-Issa & Sulieman, 2007;Hessler et al, 2018;Lin & Kennette, 2022). These evaluations also pose a risk in that faculty could change their educational choices or the courses they offer to better satisfy their customers (i.e., the student) rather than for sound pedagogical reasons (see Knutas et al, 2021), especially since they are often the basis of tenure and promotion decisions. Some teaching and learning scholars have suggested that "bad" teaching is having a teacher-centred approach while "good" teaching is more consistently focused on the student (i.e., learner-centred approach to learning).…”
mentioning
confidence: 99%